Two Perspectives on Preferences and Structural Transformation - Berthold Herrendorf; Richard Rogerson; Akos Valentinyi (Hungarian Academy of Sciences, Institute of Economics, 2011)
We assess the empirical importance of income and price effects for structural transformation in the postwar US. We explain two natural approaches to the data: sectors may be categories of final expenditure or value added; e.g., the service sector may be the final expenditure on services or the value added from service industries. We estimate preferences for each approach and find that with final expenditure income effects are the dominant forces behind structural transformation whereas with value added categories price effects are dominant. We show how the input-output structure of the US economy can reconcile these findings.
Keywords: O11; O14; 330; income effects; preferences; relative price effects; structural transformation; Strukturwandel; Einkommenseffekt; Privater Konsum; Offenbarte Präferenzen; USA